Estimating the probability of IQ impairment from blood phenylalanine for phenylketonuria patients: a hierarchical meta‐analysis. Issue 5 (30th November 2012) - Fonnesbeck, Christopher J.; McPheeters, Melissa L.; Krishnaswami, Shanthi; Lindegren, Mary Louise; Reimschisel, Tyler
Abstract: Though the control of blood phenylalanine (Phe) levels is essential for minimizing impairment in individuals with phenylketonuria (PKU), the empirical basis for the selection of specific blood Phe levels as targets has not been evaluated. We evaluated the current evidence that particular Phe levels are optimal for minimizing or avoiding cognitive impairment in individuals with PKU. This work uses meta‐estimates of blood Phe‐IQ correlation to predict the probability of low IQ for a range of Phe levels. We believe this metric is easily interpretable by clinicians, and hence useful in making recommendations for Phe intake. The median baseline association of Phe with IQ was estimated to be negative, both in the context of historical (median = −0.026, 95 % BCI = [−0.040, −0.013]) and concurrent (−0.007, [−0.014, 0.000]) measurement of Phe relative to IQ. The estimated additive fixed effect of critical period Phe measurement was also nominally negative for historical measurement (−0.010, [−0.022, 0.003]) and positive for concurrent measurement (0.007, [−0.018, 0.035]). Probabilities corresponding to historical measures of blood Phe demonstrated an increasing chance of low IQ with increasing Phe, with a stronger association seen between blood Phe measured during the critical period than later. In contrast, concurrently‐measured Phe was more weakly correlated with the probability of low IQ, though the correlation is still positive, irrespective of whether Phe was measured during the critical or non‐critical period. This meta‐analysis illustrates the utility of a Bayesian hierarchical approach for not only combining information from a set of candidate studies, but also for combining different types of data to estimate parameters of interest.